2019
DOI: 10.1029/2019jc014988
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐Basin Interactions and Water Mass Residence Times in the Western Arctic Ocean: Insights Provided by Radium Isotopes

Abstract: Radium isotopes are produced through the decay of thorium in sediments and are soluble in seawater; thus, they are useful for tracing ocean boundary‐derived inputs to the ocean. Here we apply radium isotopes to study continental inputs and water residence times in the Arctic Ocean, where land‐ocean interactions are currently changing in response to rising air and sea temperatures. We present the distributions of radium isotopes measured on the 2015 U.S. GEOTRACES transect in the Western Arctic Ocean and combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 98 publications
(246 reference statements)
4
36
1
Order By: Relevance
“…The highest 228 Ra and 226 Ra activities were found in the fresh(er) sources attributed to the surface samples collected in the western CAA ( Figure 6). The SP = 0 end-member for 226 Ra (25.2 dpm 100L -1 ) is consistent with the effective 226 Ra end-member for the Mackenzie River (26.1 dpm 100L -1 ; Kipp et al, 2019), which contributes to the freshwater budget of the CAA. Smith et al (2003) reported a Beaufort shelf end-member with a 228 Ra activity of 12 dpm -1 ).…”
Section: Iiiiiiiii Distinction Of Deep-water Masses and Indicationsupporting
confidence: 70%
“…The highest 228 Ra and 226 Ra activities were found in the fresh(er) sources attributed to the surface samples collected in the western CAA ( Figure 6). The SP = 0 end-member for 226 Ra (25.2 dpm 100L -1 ) is consistent with the effective 226 Ra end-member for the Mackenzie River (26.1 dpm 100L -1 ; Kipp et al, 2019), which contributes to the freshwater budget of the CAA. Smith et al (2003) reported a Beaufort shelf end-member with a 228 Ra activity of 12 dpm -1 ).…”
Section: Iiiiiiiii Distinction Of Deep-water Masses and Indicationsupporting
confidence: 70%
“…The increase in surface water activities caused an increase in the surface to bottom water ratios of 228 Ra and 228 Ra/ 226 Ra AR (Figure 8). The observed 228 Ra activities during all periods were within the range of historical samples from the late 1990s and early 2000s (Kadko et al, 2008;Kadko & Muench, 2005;Kipp et al, 2019;Smith et al, 2003;Trimble et al, 2004), and higher than the 228 Ra activities measured to the east during period 2 of this study (Figure 9). With the exception of the 1995 samples from the Canadian Beaufort shelf, all of the historical samples were collected slightly to the west of our study region.…”
Section: Radium Isotopes and Nutrientssupporting
confidence: 56%
“…This study area's composite wind vectors are shown in Figure 5. (Kadko et al, 2008;Kadko & Muench, 2005;Kipp et al, 2019;Smith et al, 2003;Trimble et al, 2004). For samples in the Beaufort Sea, only samples east of the Barrow Canyon are shown.…”
Section: Resultsmentioning
confidence: 99%
“…The REE data collected at the crossover station (stations HLY1502-30 and PS94-101) within 14 days compare well especially below 500 m water depth, where they are within 1 pmol L −1 for Nd and 0.5 pmol L −1 Kipp et al (2018Kipp et al ( , 2019; Rutgers van der Loeff et al 2018 Note. Refer to the publication for the sample handling and analytical methods pertaining to the TEI of interest.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 80%